Kuwait's Foreign Policy in the 2017 Gulf Crisis between Saudi Arabia-Qatar - Bulgini, Moh. Iqbal (Journal Of Middle East and Islamic Studies, 2021)
The Saudi Arabia, United Arab Emirates, Bahrain and Egypt embargoes against Qatar on June 5, 2017 have harmed the Qatari side and have broken the stability of the GCC. The involvement of Iran and Turkey on the Qatari side has made GCC fragments unavoidable. This crisis was actually triggered by Saudi Arabia's perception that Qatar had supported a terrorist movement that made Saudi Arabia invite all GCC countries to blockade Qatar, but among the Gulf countries, Kuwait is the only country that rejects the embargo and chooses neutral, even mediating the crisis.The reasons for Kuwait's rejection of the Saudi Arabian embargo and Kuwait's interest in the crisis will be analyzed using the theory of neorealism and hedging concepts.This writing uses a qualitative approach with descriptive-analytical analysis. The neorealist, neutrality and mediation of Kuwait in the 2017 Gulf crisis because Kuwait wants to "survive" in the GCC and the region, given Iran's involvement on the Qatar side while Kuwait does not want to conflict with Iran Based on the hedging strategy, Kuwait undertakes indirect balancing of Saudi Arabia such as rejecting a security pact GCC 1981, refused send troops to Bahrain 2011, and challenge the Saudis to develop economic zones on five islands involving Iran's presence. Kuwait also engaged Qatar with mediating the crisis in Qatar in 2014 and 2017.